2009
DOI: 10.1080/13032917.2009.10518913
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intention to Purchase Over the Internet

Abstract: More than 10 years on since the launch of the Internet, there are clear differential levels of adoption of the Internet for purchasing leisure travel across countries. In some countries, such as Portugal, only a minority of travel purchasing is conducted over the Internet. This paper aims to contribute to a greater understanding of adoption of purchasing over the Internet by evaluating the determinants of intention to adopt the Internet for purchasing leisure travel. A number of variables are used to assess wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…convenience, lower price, time saving and relations with persons who share common interests. In the field of tourism and ecommerce, a significant and positive relationship between perceived relative advantages and consumer behaviour intention and attitudes is supported by a wide variety of studies e.g., (Amaro & Duarte, 2015;Jensen, 2009;Kamarulzaman, 2007;Lu et al, 2011;Moital, Vaughan, Edwards, & Peres, 2009). Therefore, customers who perceive the relative advantages of online travel community are more likely to participate in online travel community.…”
Section: Perceived Relative Advantages Compatibility Attitudes Andmentioning
confidence: 97%
“…convenience, lower price, time saving and relations with persons who share common interests. In the field of tourism and ecommerce, a significant and positive relationship between perceived relative advantages and consumer behaviour intention and attitudes is supported by a wide variety of studies e.g., (Amaro & Duarte, 2015;Jensen, 2009;Kamarulzaman, 2007;Lu et al, 2011;Moital, Vaughan, Edwards, & Peres, 2009). Therefore, customers who perceive the relative advantages of online travel community are more likely to participate in online travel community.…”
Section: Perceived Relative Advantages Compatibility Attitudes Andmentioning
confidence: 97%
“…Physical effort of in-store travel shopping Christou and Kassianidis (2003) The larger the perceived physical effort of in-store travel shopping, the larger the perceived relative advantage of shopping for travel online. Overall relative advantages Christou and Kassianidis (2003); Moital, Vaughan, Edwards, and Peres (2009) Higher levels of perceived relative advantages are positively related to intentions to purchase travel online.…”
Section: Heung (2003)mentioning
confidence: 99%
“…Early studies have shown that consumers who purchase travel online were more likely to have more years of Internet experience (Card et al, 2003;Kah et al, 2008;Kamarulzaman, 2007Kamarulzaman, , 2010Kim & Kim, 2004;Weber & Roehl, 1999), spend more time online (Beldona et al, 2011;Kah et al, 2008;Kim & Kim, 2004;Morrison et al, 2001;Weber & Roehl, 1999), and have prior online shopping experience (Kim, Ma, & Kim, 2006;Moital, Vaughan, Edwards, & Peres, 2009).…”
Section: Computer/internet Knowledge and Usagementioning
confidence: 99%
“…Section B specifically focused on possible respondent motives in making use of either the travel agent or Internet, by reviewing the elements considered to be of critical importance in the decision-making process as determined through the literature study. The elements are: trust/risk (Austin et al, 2006;Izquierdo-Yusta & Martinez-Ruiz, 2011;Kim, Kim and Leong, 2005), ease of use and technological adoption (Ahmad & Juhdi, 2009;Anckar & Walden, 2002;Gianforte, 2003), empathy (Caro & Roemer, 2006;Wolfe et al, 2004), price (Cheyne et al,2006;Mayr & Zins, 2009), cross-channel behavior (Jensen, 2012;Toh et al, 2011), convenience (Buhalis & Licata, 2002;Jensen, 2012), time (Mayr & Zins, 2009;Morgan, Pritchard & Abbott, 2001), assurance (Austin et al,2006;Jarvenpaa et al, 2000), reliability (Dunn et al, 2009;Holloway & Beatty, 2008) and complexity (Moital, Vaughan, Edwards & Peres, 2009;Ryan & Rao, 2008). This section B part of the questionnaire were itemised along a 5-point Likert-type scale ranging from 1, strongly agree; 2, tend to agree; 3, tend to disagree; 4, strongly disagree; 5, not applicable.…”
Section: Methodology and Designmentioning
confidence: 99%